Local fungi, willow and municipal compost effectively remediate petroleum-contaminated soil in the Canadian North - Robichaud, Kawina; Girard, Catherine; Dagher, Dimitri; Stewart, Katherine; Labrecque, Michel; Hijri, Mohamed; Amyot, Marc (Chemosphere, 2018)
Low energy-input alternatives based on locally available products are needed for treating petroleum-hydrocarbon spills in northern regions. We tested the efficacy of three local biological components (municipal compost, white-rot fungus: Pleurotus ostreatus and willow: Salix planifolia) to remediate diesel-contaminated soils in a subarctic climate (Whitehorse, YT, Canada), and compared their efficacy to natural attenuation and chemical fertilizers (industry standard). After the first growing season, biologically amended treatments (BAT) that contained >2 biological components, had decreased 69–73% of the diesel's F2 fraction (C10-C16), which is more than natural attenuation or fertilizer (48 and 51%). By the third growing season, the BAT dropped below the Canadian Council of Ministers of the Environment's (CCME) Agricultural & Residential/Parkland guideline (<150 mg kg−1) and 86% of willows had survived and developed extensive roots. MiSeq amplicon sequencing of fungal (ITS) and bacterial (16S) rRNA genes showed the BAT's microbial communities were significantly more abundant and diverse. We found 132 bacterial and 35 fungal genera unique to the BAT. Readily-available local biological components such as municipal compost, fungi and willows may provide an effective alternative to applications of imported chemical fertilizers for the bioremediation and revegetation of diesel-contaminated soil in northern environments.